KOMBINASI PELATIHAN CABLE MACHINE WOODCHOPPER DAN MEDICINE BALL FULL TWIST LEBIH BAIK DARIPADA KOMBINASI PUSH UP KNEE DAN SIT UP DALAM LEMPAR CAKRAM - Putra Suarsana, I Putu; Tirtayasa, K; Muliarta, Made (Sport and Fitness Journal; Volume 4, No. 2, 2016, 2016)
Biomotor components of strength and speed are the base of the components ofexplosive power of muscles, especially motion tools in the upper body. The combination oftrainings that can be used to increase muscle strength and speed are cable machinewoodchopper and a medicine ball full twist training and push up knee and sit up training. Thecurrent study used an experimental design with a sample of 36 people which is taken usingproportional random sampling from the population which met the inclusion and exclusioncriteria and dividen into two groups. Each group consist of 18 people. The combinationtraining between cable machine woodchopper and medicine ball full twist was used by theGroup I, while the combination between training push up knee and sit up was used by theGroup II. The study was conducted three times a week for 6 weeks. Data were collected fromthe result of the discs throw before and after the study. The collected data were statisticallyanalyzed. From the analysis, it was obtained that the variant of data was homogeny and thedistribution was normal. Therefore, the analysis continued with the paired t-test and independent t-test. The paired t-test result showed that there is a increase number of results indiscus throw on both of the experiment groups (p <0.05). While the independent t-testsshowed that before the training in the group I and group II found was not significantlydifferent (p> 0.05), but after the training between group I and group II are equally increasedtheir results in discus throw (p <0.05). From the results, it can be inferred that thecombination between cable machine woodchopper and medicine ball full twist training inGroup I increased higher than the combination between push up knee and sit up training inGroup II on the outcome of discus throwing.
Keywords: cable machine woodchopper, medicine ball full twist, push up knee and sit up, results discus throw